1991
DOI: 10.1113/jphysiol.1991.sp018563
|View full text |Cite
|
Sign up to set email alerts
|

The roles of catecholamines in responses evoked in arterioles and venules of rat skeletal muscle by systemic hypoxia.

Abstract: SUMMARY1. Studies have been made in the anaesthetized rat of the roles played by a-and /8-adrenoreceptor stimulation in determining diameter changes induced in individual arterioles and venules of the spinotrapezius muscle during systemic hypoxia (breathing 6% 02 for 3 min).2. Topical application to the spinotrapezius of phentolamine, the cz-adrenoreceptor antagonist, or sotalol, the ,3-adrenoreceptor antagonist, had no effect on the fall in systemic arterial pressure and tachyeardia induced by hypoxia.3. All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 22 publications
7
20
0
Order By: Relevance
“…Moreover, the sections of the arteriolar tree that were most affected were the primary and secondary arterioles of 18-40 µm that are most strongly constricted by direct stimulation of the sympathetic nerves (81). More detailed analysis of each section of the arteriolar tree showed that only vessels that constricted in hypoxia were affected by phentolamine, while those that dilated were not (86). These observations are consistent with the occurrence of an increase in sympathetic nerve activity to skeletal muscle during systemic hypoxia, as would be expected from the primary response to carotid chemoreceptor stimulation (see above) and suggest that the sympathetic nerve activity preferentially constricts the primary and secondary arterioles.…”
Section: Interactions Between Reflex and Local Effects Of Hypoxia In supporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, the sections of the arteriolar tree that were most affected were the primary and secondary arterioles of 18-40 µm that are most strongly constricted by direct stimulation of the sympathetic nerves (81). More detailed analysis of each section of the arteriolar tree showed that only vessels that constricted in hypoxia were affected by phentolamine, while those that dilated were not (86). These observations are consistent with the occurrence of an increase in sympathetic nerve activity to skeletal muscle during systemic hypoxia, as would be expected from the primary response to carotid chemoreceptor stimulation (see above) and suggest that the sympathetic nerve activity preferentially constricts the primary and secondary arterioles.…”
Section: Interactions Between Reflex and Local Effects Of Hypoxia In supporting
confidence: 76%
“…Our observations on the effects of antagonists of the actions of circulating hormones are comparable with those just described in that a vasopressin receptor antagonist affected the arterioles that constricted in response to systemic hypoxia, but had no effect on those that dilated (88), whereas a ß adrenoreceptor antagonist affected the arterioles that dilated in response to systemic hypoxia, but had no effect on those that constricted (86). These observations were in turn consistent with evidence that vasopressin is released in response to selective stimulation of carotid chemoreceptor and that vasopressin receptor blockade reduces the increase in gross muscle vascular conductance induced by systemic hypoxia (89) and with evidence that adrenaline is released into the blood stream by hypoxic stimulation of carotid chemoreceptors and makes a contribution, albeit small, to the hypoxia-induced increase in gross muscle vascular conductance (90).…”
Section: Interactions Between Reflex and Local Effects Of Hypoxia In supporting
confidence: 72%
“…The increase in NO output evoked by adenosine infusion was probably the result of generation of NO by endothelial NOS (eNOS) rather than by neuronal NOS (nNOS) present in skeletal muscle or sympathetic neurones (Michel & Feron, 1997), as adenosine is rapidly taken up and metabolized by endothelial cells and is unlikely to have reached extravascular tissues (see Ray et al 2002). Further, the evidence available suggests that the adenosine released during systemic hypoxia is of endothelial, rather than skeletal muscle origin (see Mian & Marshall, 1991 b ; Mo & Ballard, 2001; Edmunds et al 2003). Thus, it is likely that this endogenous adenosine acts back on the endothelial cells via A 1 receptors to stimulate eNOS and release NO.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence indicates this arises firstly because the dilator influence of adenosine is partly mediated by NO and a tonic level of NO is required for adenosine to be released from the endothelial cells by hypoxia (Ray et al 2002; Edmunds et al 2003; Ray & Marshall, 2005). Secondly, it is likely that NO synthesis is required for that part of the action of adenosine and of other dilator substances released in systemic hypoxia, such as adrenaline, that rely on an increase in cAMP (see Mian & Marshall, 1991; Edmunds et al 2003). For cGMP and cAMP are synergistic in producing vasodilatation, and thus a decrease in cGMP induced by inhibition of NOS not only reduces vasodilatation evoked by agonists that act via NO, but those that act by increasing cAMP (de Wit et al 1994).…”
mentioning
confidence: 99%